Modern features and problems of forming balanced economic growth and development of the Republic of Tatarstan - V. V. Stroev; V. M. Svistunov; S. V. Sidorenko (Управление)
This paper examines the theoretical foundations and provisions for the formation of balanced economic growth and development of the region considering its territorial, socio-economic, resource, and structural features and using the Republic of Tatarstan as an example. The paper analyses the theoretical and methodological apparatus proposed by scientists and specialists in ensuring the economic growth and development of the region. The purpose is to identify the main risks, factors and problems in the economic sectors of the Republic of Tatarstan, which to one degree or another are capable of influencing the processes of forming the balanced economic growth and development of the region. Based on the analysis, the paper identifies common problems for the regions and formulates the main directions for improving the economic situation in the region, and also submits for consideration the authors’ model of interaction between enterprises, state and municipal entities in order to reduce the negative impact of previously identified threats and problems, which considers new global challenges, transformations and restructures in economic processes associated with the introduction of restrictive measures, political isolation, various economic sanctions, and with the unresolved internal problems in the field of the economic growth and development of the Republic of Tatarstan.